2015
DOI: 10.1073/pnas.1424636112
|View full text |Cite
|
Sign up to set email alerts
|

Ideal probe single-molecule experiments reveal the intrinsic dynamic heterogeneity of a supercooled liquid

Abstract: The concept of dynamic heterogeneity and the picture of the supercooled liquid as a mosaic of environments with distinct dynamics that interchange in time have been invoked to explain the nonexponential relaxations measured in these systems. The spatial extent and temporal persistence of these regions of distinct dynamics have remained challenging to identify. Here, singlemolecule fluorescence measurements using a probe similar in size and mobility to the host o-terphenyl unambiguously reveal exponential relax… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

7
71
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(78 citation statements)
references
References 33 publications
7
71
0
Order By: Relevance
“…Many other studies are consistent with τ ex ≈ 3τ α , where τ ex is the time a mode retains its time constant (6,7). The time until one mode has experienced all possible environments and thus restored ergodicity has to be much longer than τ ex , as found in the ideal-probe single-molecule work of Paeng et al (2). This single-molecule approach to the dynamics of glass-forming materials may also have the potential to directly observe the nontrivial length scales (Fig.…”
supporting
confidence: 56%
See 1 more Smart Citation
“…Many other studies are consistent with τ ex ≈ 3τ α , where τ ex is the time a mode retains its time constant (6,7). The time until one mode has experienced all possible environments and thus restored ergodicity has to be much longer than τ ex , as found in the ideal-probe single-molecule work of Paeng et al (2). This single-molecule approach to the dynamics of glass-forming materials may also have the potential to directly observe the nontrivial length scales (Fig.…”
supporting
confidence: 56%
“…Therefore, the ideal method for studying the dynamics of materials is by an experiment that allows us to look at the sample one molecule at a time. Relative to previous single-molecule studies, the recent advance reported by Paeng et al (2) is based on using a probe molecule that reflects the liquid's behavior with high fidelity.…”
mentioning
confidence: 99%
“…These observations imply that deeply supercooled liquids exhibit spatially heterogeneous dynamics (29)(30)(31). Dynamic heterogeneities have been confirmed by direct observations of several single fluorescent molecules immersed in ortho-terphenyl (32) or nanorods immersed in glycerol (33). Physically different systems also show analogous behavior.…”
mentioning
confidence: 66%
“…[1][2][3][4][5] Relevant applications include gas and molecule separations, 6 water purification membranes, 7 barrier materials, self-healing systems based on microcapsules, [8][9][10] ion and solute transport in polymeric materials and biological systems, 11 and the flow of colloids in porous media. 12,13 Penetrants are here, by definition, smaller than the elementary species that constitutes the matrix, but they can still vary over a wide range of absolute and relative size and shape and the extent of attractive interactions with the matrix material.…”
Section: Introductionmentioning
confidence: 99%